Bowel Ischemia from Heat Stroke: A Rare Presentation of an Uncommon Complication - Umair Masood; Anuj Sharma; Wajihuddin Syed; Divey Manocha (Case Reports in Medicine)
A healthy 27-year-old female presented to the hospital after she collapsed an hour into her first marathon run on a hot humid day. On presentation, she was hyperthermic, encephalopathic, tachycardic, and hypotensive. On admission, she was found to have lactic acidosis, rhabdomyolysis, and acute kidney injury and was treated with cold normal saline and cooling blankets. She subsequently started having abdominal pain and bloody bowel movements. Computed tomography of the abdomen revealed ascending colon thickening. Furthermore, her lab findings showed transaminitis and elevated coagulation parameters. Due to the acute hypotensive state from the heat stroke, patient had developed bowel ischemia, ischemic hepatitis, and disseminated intravascular coagulation, all of which are uncommon complications of heat stroke. She was managed aggressively with intravenous fluid hydration with resolution of her symptoms over the course of 4 days. In addition to the uncommon complications, early presentation of this bowel ischemia despite adequate hydration in such a healthy individual is another unique aspect of the case.